Circular polarization of the high energy electron bremsstrahlung with account of the second Born approximation - Shul’ga, N.F.; Syshchenko, V.V. (Вопросы атомной науки и техники, 2007)
The estimation of contribution of the second Born approximation into circular polarization of bremsstrahlung from linearly polarized electrons is obtained. Account of this contribution could be important for correct interpretation of results of measurements of fine effects due to weak interactions.